PENGEMBANGAN KAPASITAS BADAN USAHA MILIK DESA (BUMDES) DI DESA TASIK SERAI BARAT KECAMATAN TALANG MUANDAU KABUPATEN BENGKALIS TAHUN 2023 - Cahyani, Gita; Rafi, M. (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
Capacity development is one component in increasing the capabilities possessed by a government organization, with the aim of being able to carry out the main tasks and functions in government. Village-Owned Enterprises (BUMDes) are business entities owned and managed by villages, with the aim of improving the welfare of village communities and increasing village original income (PAD). The BUMDes Jambu Berseri Tasik Serai Barat Village, which was founded in 2015, has 3 business units, namely savings and loans, agriculture and office stationery photocopying. This research uses capacity development theory by Grindle in Haryono which explains that capacity development can be viewed from several dimensions, namely human resource development, organizational strengthening and institutional reform. This research is a study with a descriptive qualitative approach that uses primary and secondary data to answer the research objectives systematically. The results of this research indicate that the capacity development of Village-Owned Enterprises (BUMDes) in Tasik Serai Barat Village, Talang Muandau District, Bengkalis Regency in 2023, is still not optimal. First, in the human resource development dimension, there is still a lack of training carried out by BUMDes managers so that the performance of BUMDes managers is still not optimal in developing business units. Second, the dimension of organizational strengthening is caused by the lack of infrastructure to support business unit activities. Third, institutional reform is still hampered by an inadequate budget. Keywords: Capacity Development, BUMDes.